Does Upper Arm Length, Arm Span, and Foot Length Serve as Good Predictors for Stature? A Cross-Sectional Study among Northern Nigerians - , Loveday Ese Oghenemavwe, Hakeem Babatunde Fawehinmi, Peter Done Okoh, Lekpa Kingdom David, Michael Anozie Amadi, Chile A. Oparaocha, Celestine Ebieto Ebieto, Priscilla Nkechinyere Nwofor, Nicholas Asiwe (Archives of Current Research International, 2024)
Background: Stature estimation is an important identification process in the field of physical and forensic anthropology and for industrial design. The study aims to determine if upper arm length, foot length, and arm span could be good predictors for stature among northern Nigerians. Methods: The study adopted a descriptive cross-sectional design using a multi-stage random sampling technique. 400 northern Nigerians (200 males and 200 females) were involved in the research and data were collected via direct anthropometric method using a stadiometer, and meter rule. The data obtained were analyzed using the IBM SPSS and probability was stated (p<0.05). Results: The findings of the study show that males have a mean value for the standing height, upper arm length, foot length, and arm span as 171.97±6.68 cm, 32.62±2.55 cm, 25.76±1.17 cm, 181.72±7.83 cm respectively, and females were 163.33±5.96 cm, 35.23±2.19 cm, 23.04±1.51 cm, and 168.67±6.68 cm for standing height, upper arm length, foot length, and arm span which has shown sexual differences and age-related differences (p<0.05). The upper arm was found to be a weak predictor for stature (R=0.045, SEE=7.66), foot length and arm span were good predictors of stature (R=0.73, SEE=5.24 and R=0.83, SEE=4.25) univariately. Multivariate analysis of the upper arm length, foot length, and arm span were better predictors for stature (R=0.85, SEE=4.07). Conclusion: The foot length and arm span are good predictors of stature and the findings will be useful to forensic anthropologists